Analysis of changes in the flow of mixtures of natural gas and hydrogen in pipelines network - Szoplik, Jolanta; Ciuksza, Marta (Instal, 2021)
The study analyzed the results of simulating the flow of gas, gas mixtures and hydrogen (15% or 30% by volume) or pure hydrogen in the low pressure gas pipeline network. The calculations were made on the basis of data on the actual network load with high-methane natural gas for four selected ambient temperatures. The results of the overpressure distribution of gas-hydrogen or pure hydrogen mixtures in the network pipelines were analyzed for the maximum value of the overpressure of the stream fed to the network, and then for each mixture and the ambient temperature, the value of the minimum overpressure of the stream supplying the network was selected. The test results were compiled in the form of a relationship that allows the estimation of the minimum flow overpressure depending on the hydrogen content in the mixture. It has been shown that when transporting hydrogen or gas-hydrogen mixtures, the network load increases, which requires an increase in the overpressure of the stream at the entrance to the network, which may be even greater than the maximum overpressure allowed for the low pressure network.
Keywords: low pressure gas pipeline network; gas flow simulations; transport of hydrogen or gas mixtures; distribution of overpressure in the network